Studi Eksperimental Tentang Head Loss Pada Aliran Fluida Yang Melalui Elbow 90° - -, Helmizar (Jurnal Energi Dan Manufaktur, 2012)
Factors that cause energy loss in a piping system is something that is interesting and important to be studied moredeeply. 90° Elbow is a common connection in piping systems. Elbow 90° contributes to the incidence of head loss. Thisresearch will try to identify the influence of curvature (R/d) to the head lossThis study uses test model 90 ° elbows connection with the variation of the radius of curvature of the connectionelbow 90 ° to the pipe diameter (R / d) of 4.199 and 6.299. Flow rates are varied with Q1 = 0.000312345986 m3/s and Q2 =0.000265776 m3/s.The experimental results show that the R/d = 6.299 have a greater head loss rather than the R/d = 4.199. Strikingdifferences in the distribution of pressure coefficient between the radius of inner and outer radius. favorable pressuregradient phenomena occur on the inner radius. Events adverse pressure gradient at the outer radius of elbow allegedlycontributing to the loss of energy / head loss at the elbow 90 °.
Keywords: elbow 90°, head loss, radius of curvature,pressure coefficient, adverse pressue gradient, favorable pressure gradient